Recent Publications (Quarterly Journal of Economics, 1960)
Recent Publications Get access The Quarterly Journal of Economics, Volume 74, Issue 2, May 1960, Pages 338–339, https://doi.org/10.1093/qje/74.2.338 Published: 01 May 1960